A novel referral strategy to enhance the enrollment of patients with heart failure in cardiac rehabilitation: A feasibility study - Anne Mette Schmidt; Jannie Rhod Bloch‐Nielsen; Helene Nørgaard; Loui Hannibal; Sarah Holm Junge Jensen; Lars Hermann Tang; Nanna Rolving (Health Science Reports, 2024)
Abstract Background and Aims Rehabilitation targeting patients with cardiac conditions are evident and acknowledged in clinical guidelines. However, participation rates remain suboptimal, with only 50% of all patients with cardiac conditions participating in these programs across Europe. Considering the well‐documented effects of rehabilitation, increasing the referral rate to cardiac rehabilitation would be desirable. This study aimed to evaluate the feasibility of a novel referral strategy that could potentially enhance enrollment in cardiac rehabilitation for patients with heart failure. Methods This prospective feasibility study incorporating both quantitative and qualitative methods was conducted in an outpatient heart failure clinic and a municipal health care center. 106 patients with heart failure were referred to the heart failure clinic from September 2021 through July 2022. A 15−20 min face‐to‐face physiotherapy consultation was incorporated into usual care, evaluating patients' habitual and actual level of functioning, disability, and physical activity and assessing their potential need and motivation for cardiac rehabilitation. Three predefined quantitative feasibility outcomes: reach, referral rate, and data completeness were assessed. Additionally, semi‐structured interviews explored acceptability among patients and health care professionals at the municipal health care center and the hospital. Finally, the potential effect was assessed based on the enrollment rate. Results Physiotherapy consultations were offered to 86% of eligible patients; of these, 52% were referred to cardiac rehabilitation. Ninety‐one percent data completeness was achieved. The intervention was well‐accepted by patients and health care professionals. The enrollment rate reached 79%. Conclusion The novel referral strategy proved feasible concerning reach and data completeness, although the referral rate suggested that further refinements are required before a full‐scale trial. The novel referral strategy was well‐accepted, and enrollment rate approached an acceptable level.